Swiss cheese disease: A rare case of juvenile papillomatosis of the breast mimicking carcinoma in a young female - Ronak Hameed; Ajith Vettuparambil (Wolters Kluwer Medknow Publications, 2023)
Juvenile papillomatosis is a rare benign proliferative lesion of breast seen in young females. These patients have been reported to have a strong family history for carcinoma breast. It is rarely diagnosed preoperatively but has distinct histopathological features on postoperative examination. The subsequent treatment and prognosis vary accordingly. Here, we report a case of a 38-year-old female who was operated with a preliminary diagnosis of Mucinous carcinoma of left breast.